Mutational analysis of the Notch2 negative regulatory region identifies key structural elements for mechanical stability - Natalie L. Stephenson; Johanna M. Avis (FEBS Open Bio, 2015)
The Notch signalling pathway is fundamental to cell differentiation in developing and self‐renewing tissues. Notch is activated upon ligand‐induced conformational change of the Notch negative regulatory region (NRR), unmasking a key proteolytic site (S2) and facilitating downstream events. The favoured model requires endocytosis of a tightly bound ligand to transmit force to the NRR region, sufficient to cause a structural change that exposes the S2 site. We have previously shown, using atomic force microscopy and molecular dynamics simulations, that application of force to the N‐terminus of the Notch2 NRR facilitates metalloprotease cleavage at an early stage in the unfolding process. Here, mutations are made within the heterodimerization (HD) domain of the NRR that are known to cause constitutive activation of Notch1 whilst having no effect on the chemical stability of Notch2. Comparison of the mechanical stability and simulated forced unfolding of recombinant Notch2 NRR proteins demonstrates a reduced stability following mutation and identifies two critical structural elements of the NRR in its response to force – the linker region between Lin12‐Notch repeats LNRA and LNRB and the α3 helix within the HD domain – both of which mask the S2 cleavage site prior to Notch activation. In two mutated proteins, the LNRC:HD domain interaction is also reduced in stability. The observed changes to mechanical stability following these HD domain mutations highlight key regions of the Notch2 NRR that are important for mechanical, but not chemical, stability. This research could also help determine the fundamental differences in the NRRs of Notch1 and Notch2.